Additive manufacturing in community pharmacies: a framework for business model innovation. Issue 3 (16th March 2021) - Feldmann, Carsten; Rose, Olaf
Abstract : Background: Additive manufacturing offers new opportunities in that it brings the preindustrial production back into community pharmacies. Methods: This study was based on the qualitative research methodology of action research. The 55 domains of the St. Gallen Business Model Navigator were applied to three-dimensional drug printing (3DDP) from the pharmaceutical and the economic perspectives. Results were synthesised and applied to a model of potential customer drivers. Results: This study classified 55 relevant business models into a framework to systematise business model innovations. Out of the potential 55 business model patterns, 27 have been identified as suitable for implementation. Promising examples of business model characteristics are to foster customer loyalty by convenience and therapeutic benefits, to offer an individualised shopping experience, to provide a guaranteed availability, to leverage customer data for selling additive services, to create value in a specialised niche, to create mass customisation and to offer ultimate luxury. Conclusion: A reference model to systematise promising business model patterns for practitioners was developed, providing initial indications for implementation of 3DDP in community pharmacies. Pharmacies innovating or extending their business models can strengthen their positions in the value chain, create competitive advantages and expand into new markets.